Sindroma Pre Eksitasi Asimtomatik: Ablasi Versus Konservatif - Dian Andina Munawar; Yoga Yuniadi (The Indonesian Heart Association, 2013)
Wolff-Parkinson-White (WPW) is a sporadic and familial abnormality. Epidemiologicaldata indicate that 0.1% to 0.3% of the general populationhave ECG findings suggesting that during sinus rhythm. The risk of suddencardiac death is around 0.25%. Patients with WPW syndrome is oftensymptomatic because of cardiac arrhythmias. Sometimes the arrhythmiacan be life-threatening, and leads to sudden cardiac death. However, thereis still controversy in management of individuals with asymptomatic WPWpattern. Despite radiofrequency catheter ablation remains the first linetherapy of the WPW syndrome, the risk of complications of this procedureis almost the same as the risk of sudden cardiac death in asymptomaticWPW. Therefore, an algorithm to determine the appropriate managementof asymptomatic WPW patients is needed.